Loss and trauma in Le Fils and Manchester‐by‐the‐Sea: Redemption as resilience. Issue 4 (5th December 2018) - Nelson, Derek R.
Abstract: Resilience is emerging as a key concept in many disciplines to describe durability of designs, communities, institutions, and even persons. This article considers how "resilience" might be related to the "redemption" of past wrongs committed and evil suffered. Resilience functions as a kind of God‐given holding pattern so that healing can begin and amends be made. Two films, Le Fils (The Son) and Manchester‐by‐the‐Sea, present examples of characters who endure awful trauma, yet who find sources of strength outside of themselves to help keep them open to an experience of redemption.